Transjugular intrahepatic portosystemic shunt: Where are we? - Altun, Reskan; Yıldırım, Emre; Öcal, Serkan; Akbaş, Enver; Harman, Ali; Korkmaz, Murat; Selçuk, Haldun (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The purpose of this study was to evaluate the technical/hemodynamic success, complications, and biochemical/ hematologic consequences of transjugular intrahepatic portosystemic shunt (TIPS) created with 10-mm bare stents in our patients. Materials and Methods: Data of 27 cirrhotic patients (18 men and 9 women; mean age, 39.7±18.7 years) with a median MELD score 14 (range 7-31) treated with TIPS between January 2000 and August 2010 were evaluated retrospectively. Results: The indications were refractory bleeding varices in 48.2%, refractory ascites in 22.2%, and Budd-Chiari syndrome in 29.6% of the patients. Technical and hemodynamic success rates were 96.3% and 92.3%, respectively. Mean portosystemic pressure gradient decreased from 21.5±5.3 mm Hg to 9±2.7 mm Hg (p<0.05). The rate of primary stent patency was 76.9% 1 year after the procedure. No statistically significant difference in shunt dysfunction was found between the groups of patients treated for Budd-Chiari syndrome and other indications (p>0.05). One patient (3.7%) had shunt dysfunction due to thrombosis within 24 hours. New and/or worsening hepatic encephalopathy occurred in 34.6% of patients. Increased age (≥40 years) was significantly related to hepatic encephalopathy in both univariate and multivariate analyses (p<0.05). Thirty-day mortality rate and 1-year transplant-free survival rate were 0% and 80.7%, respectively. Conclusion: Transjugular intrahepatic portosystemic shunt procedure is a safe treatment for many patients with cirrhosis, but post-procedure hepatic encephalopathy and shunt dysfunction are still problems. Especially, patient age should be taken into consideration in predicting hepatic encephalopathy risk.